The Correlation of Radiogenomics and Green Tea Extract Polyphenols: Redefining Head and Neck Cancer Management - Tenguria, Manish; Bahuguna, Nikita; Garg, Nikhil; Singh, Deependra Pratap; Gupta, Payal; Gupta, Meenu; Rai, Nishant (Asian Pacific Journal of Cancer Care, 2025)
Radiogenomics, an emerging paradigm that combines genomic and imaging information, is poised to advance precision oncology, particularly in head and neck cancer (HNC). This review explores the potential integration of radiogenomics with the polyphenol epigallocatechin-3-gallate (EGCG) from green tea, building on systematic and bibliometric analyses of an unprecedented amount of information (molecular and clinical milestones and advances) related to oncology and radiogenomics, spanning from 1997 to 2024. Including an antioxidant and anticancer compound, EGCG has shown promise in modifying the response to radiation and modifies certain biologic pathways. It is proposed that radiogenomic markers will be effective in modifying toxicity, potentially augmenting precision treatments in HNC, while simultaneously integrating the fields of genetics, imaging, and nutraceuticals into one new area for future research and clinical practice.